Guideline Compliance in Surgery for Thyroid Nodules – A Retrospective Study - Reinisch, A.; Malkomes, P.; Habbe, N.; Bojunga, J.; Grünwald, F.; Badenhoop, K.; Bechstein, W. O.; Holzer, K. (Experimental and Clinical Endocrinology & Diabetes, 2017)
Diagnostic guidelines for thyroid nodules focus on malignancy risk assessment to avoid unnecessary diagnostic operations. These guidelines recommend a combination of tests in form of a diagnostic algorithm. The present study analyzed the recommended algorithm and its implementation by different medical professionals. Preoperative diagnostic procedures, laboratory tests and histopathological findings of patients who underwent thyroid surgery between 2006 and 2013 were analyzed. The results were stratified by the assignation by specialized endocrinologists (ENP), general practitioners (GP) or Goethe-University Hospital Frankfurt (UKF). 677 patients were enrolled, of these 62% were assigned by UKF, 18.5% by an ENP and 19.5% by a GP. Ultrasonography rate was significantly higher in UKF (97.6%) compared to patients assigned by GP (90.9%, p<0.0001). Rates for fine-needle aspiration cytology ranged between 47.6% in UKF and 23.2% in ENP (p<0.0001). In over 93% of the patients an analysis of thyroid-stimulating hormone and triiodothyronine/thyroxin was realized. The overall malignancy rate was 11.82%. The malignancy rate was significantly higher if a FNA biopsy was performed (16.35 vs. 8.94%; p=0.0048). A higher malignancy rate could only be seen if the preoperative diagnostic workup included FNA. Besides this, the grade of algorithm adherence showed no effect on the malignancy rate.
Keywords: thyroid cancer; thyroid nodules; diagnostic algorithm; diagnostic operations; guidelines